El papel de la movilidad estudiantil en el desarrollo de la competencia comunicativa intercultural: un estudio de caso - Šifrar Kalan, Marjana (Studia Romanica Posnaniensia, 2021)
The objective of this case study is to investigate the role of student mobility in the development of intercultural communicative competence in university students. In order to indicate the changes in the participants, especially about their attitudes towards Spanish culture, Spaniards and their stereotypes, an interpretative research with an ethnographic approach has been carried out, namely, we have interviewed several students of Hispanic Philology from the University of Ljubljana (level C1 of Spanish), who had spent at least one semester with the Erasmus scholarship studying in Spain. The article does not pretend to achieve a statistical generalization due to its limited sample, however it can be useful as a preliminary study.